Investigations Of Transmission Losses And Efficiency - Osahenvenwen O.A.; Enoma O.C.; Aitanke H. (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2018)
This study presents Evaluation of transmission losses and efficiency, aim at to determine the losses associated with power transmission line and provide solution to improve power transmission line. This study was carried out at Benin regional power transmission station on 330KV/132KV power network, Sapele Road, Benin City. The Data collected were hourly reading recorded by various system operators on duty on a twenty-four hour basis, for duration of one year, from July 2009 to June 2010. Data collected were transmission parameters such has the sending voltage, Current and Power from Delta 330KV power station to Benin 330 KV received power station with voltage, current and power. In addition, 132KV transmission line parameters were also considered. The average voltage loss per month from 132KV transmission line from Benin to Irrua is 2.67KV, while the current is 16.25 Amp. The average voltage loss per month on 330KV transmission line from delta to Benin power regional centre is 4.725KV. While the current obtained is 22.5Amp. It observed that the higher power transmitted the higher the losses associated with the power system. In addition, size of cable and the distance covered are major factor that lead to loss on the power transmission line.